Health Care Transitions for Adolescents and Young Adults With Special Health Care Needs: Where Are We Now? - Mubanga, Nicole (J Patient Cent Res Rev, 2017)
Eventually, all adolescents must “graduate” from pediatric-oriented to adult-oriented health care. This transition, most often occurring during young adulthood, is especially important for adolescents with special health care needs and involves not only primary care physicians, but also both pediatric and adult subspecialists. Several studies support the benefit of transitional programs for adolescents and young adults with special health care needs. Additionally, the American Academy of Pediatrics named transitional care as one of its top priorities. However, transitional programs have yet to become an established norm among hospitals and providers, specifically outside of children’s hospitals. This topic synopsis aims to draw attention to this important issue, review the rationale behind current recommendations and report the current status of transitional programs in North America. Moreover, the steps that individual clinicians, practices and health systems may take to plan for successful health care transitions are discussed.